Modelling adrenal steroid profiles to inform monitoring guidance in congenital adrenal hyperplasiaResearch in context - Neil R. Lawrence; Jeremy Dawson; Zi-Qiang Lang; Alessandro Prete; Elizabeth S. Baranowski; Lina Schiffer; Angela E. Taylor; Aude Brac de la Perrière; Angelica Lindén Hirschberg; Anders Juul; Deborah P. Merke; John Newell-Price; et al. (EBioMedicine)
Summary: Background: There is no consensus on how to monitor adrenal androgens in Congenital Adrenal Hyperplasia (CAH). Methods: Modelling of serum and salivary steroid profiles in healthy participants and patients with CAH randomised to either standard treatment or modified-release hydrocortisone hard capsules (MRHC). Findings: Changes in serum 17-hydroxyprogesterone (17OHP) and androstenedione (A4) paralleled each other in healthy participants (n = 19) and patients with CAH (n = 122). However, healthy participants had similar absolute levels of 17OHP and A4 whereas patients with CAH had proportionally higher levels of 17OHP. Cross-correlation showed no lag between serum 17OHP and A4. In CAH, Bayesian multiple change point analysis converged on a 17OHP of 4.5 nmol/l below which in proportion to 17OHP the A4 is lower. Patients on standard treatment had a morning peak in 17OHP and A4 whereas patients on MRHC had relatively flat profiles. Salivary androgens including 11-ketotestosterone correlated with serum 17OHP and A4 in female patients (r = 0.7 to 0.9). Interpretation: In CAH, elevated 17OHP drives the production of A4. High A4 reflects poor control, but low A4 does not indicate overtreatment. Accepting 17OHP is higher than A4, both measurements give similar reflection of control, and a 17OHP <38 nmol/l (1250 ng/dl) was associated with an A4 in the normal range <5 nmol/l (143 ng/dl) in 95% of patients and in clinical trials was used to define good control. On MRHC, which controls androgen levels over 24 h, a single sample of 17OHP and/or A4 can be used to monitor control. Salivary measurements reflect similar results to serum. Funding: Diurnal; MRC; NIH; NIHR.